KAJIAN IMPLEMENTASI MANAJEMEN PAJAK PPH BADAN SERTA DAMPAKNYA TERHADAP LABA KENA PAJAK - Supriyanto, Joko; Malik, Adinda; Ilmiyono, Agung Fajar (Program Studi Akuntansi, Universitas Kuningan, 2025)
This research aim to find out the implementation of Corporate Income Tax management showing implications for the amount of taxable profit on companies in the Plastic and Packaging Sub-Sector. This research method is descriptive analysis (non-statistical). The results of the study show that Plastic and Packaging Sub-Sector companies listed on the IDX in 2020-2022 have not carried out optimal tax management. This can be seen from the effective tax rate which still exceeds the corporate tax rate and the existence of Tax Assessment Letters (SKP) and Tax Bills (STP) which create additional tax burdens. However, the company has made fiscal corrections to calculate tax profit. The results of the study also show that the effectiveness of tax management does not affect taxable profit, except for the implementation of Corporate Income Tax management with fiscal correction parameters for other temporary and permanent ones that affect taxable profit.Keywords: Tax Management, ETR, Temporary and Permanent Differences, Taxable Profits